THE INFLUENCE OF FLEXIBLE WORKING SPACE ON ACCOUNTING INFORMATION SYSTEMS EFFECTIVITY - Masnul, Mazli Wardhani; Maksum, Azhar; Bukit, Rina; Junita, Afrah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Accounting information system (AIS) is an organizational component that is responsible for preparing financial information to assist management in making decisions. Utilization of AIS will improve quality, reduce costs, increase the accuracy of decision making and share knowledge. A reliable accounting information system as a means of information in implementing state expenditure should be implemented and does not experience obstacles in its implementation even through implementation of flexible working space. It is hoped that changes to the work system through flexible working spaces will continue to support the achievement of the effectiveness of the accounting information system run by the organization. This research analyzes the effect of implementing flexible working space on the effectiveness of accounting information systems, with the research population being the State Treasury Office and its counterparts in the North Sumatra region. Research data was obtained through a questionnaire on Google Form and processed using Structural Equation Modeling (SEM) using smartPLS application. The results of this study indicate that FWS has a positive and significant effect on AIS effectiveness.